Effectiveness of a 10-week group program based on Dialectical Behaviour Therapy skills among patients with personality and mood disorders: findings from a pilot study. (October 2017) - Conrad, Agatha M; Sankaranarayanan, Anoop; Lewin, Terry J; Dunbar, Anna
Objectives: Community mental health services are often required to manage people experiencing repeated crises. Personality disorders are not uncommon, accounting for up to one-third of such presentations. These patients are often difficult to treat, leading to a revolving-door phenomenon. This study evaluated the effectiveness of a pilot intervention in reducing psychological symptoms and distress, and examined the impact of the intervention on mental health service utilization. Methods: A pre- versus post-treatment evaluation was conducted of the effectiveness of a 10-week group psychological intervention based on Dialectical Behaviour Therapy skills, conducted in a regional Australian community mental health service with patients diagnosed with either Cluster B personality disorder or a mood disorder. Results: Of those who completed the program ( N = 38 patients), 84% were female, with an average age of 35.13 years. Participants were active clients of the service for an average of 58.3 weeks prior to the program. They demonstrated significant improvements in quality of life and self-control, and a reduction in hopelessness, cognitive instability and dependence on mental health services. Conclusions: Limiting the Dialectical Behaviour Therapy program to a short-term skills-based group component was successful with the targeted patient group; however, more research is required to establish the generalizability of these results.